Antimicrobial effectiveness of polyhexamethylene biguanide on Enterococcus faecalis, Staphylococcus epidermidis and Candida albicans - Ivana Medvedec Mikić; Livia Cigić; Darko Kero; Danijela Kalibović Govorko; Goranka Prpić Mehičić; Arjana Tambić Andrašević; Paris Simeon (Medicinski Glasnik, 2018)
Aim To evaluate the antimicrobial activity of 0.2% polyhexamethilene biguanide (PHMB) in root canal models infected with Enterococcus faecalis, Candida albicans and Staphylococcus epidermidis. PHMB was compared in these tests with 2.5% NaOCl and 0.2% CHX. Methods Prepared models of 50 human root canals (n=50) were immerged in mixed, four- weeks old culture that consisted of E .faecalis, S. epidermidis and C. albicans. Roots were randomly divided into three groups: one with 30 (n=30) and two with 10 (n=10) samples. Samples were treated with polyhexamethylene biguanide (PHMB) (0.2%), sodium hypochlorite (NaOCl) (2.5%) and chlorhexidine (CHX) (0.2%), respectively. Root dentin was sampled before and after the tretment with these solutions. Colony- forming units (CFU) were counted to asses the antimicrobial effects of three solutions on viability of selected microrganisms in specimens before and after the treatment.T-test was used for comparison of results between specimens before and after the treatment, while Newman-Keuls test was used for pairwise comparison at p=0.05. Results The PHMB was significantly more efficient in reducing the number of all three tested microorganisms. NaOCl and CHX made only statistically significant (p<0.05) difference in case of E. faecalis and S. epidermidis. In the case of C. albicans, this difference was not statistically significant due to the small number of positive samples and high initial dispersion of results. Conclusion Both solutions PHMB and NaOCl were successful in eliminating E. faecalis and S. epidermidis from the mature dentin biofilm, CHX was not successful enough.